2019
DOI: 10.3389/fimmu.2019.02272
|View full text |Cite
|
Sign up to set email alerts
|

Murine Fecal Microbiota Transplantation Alleviates Intestinal and Systemic Immune Responses in Campylobacter jejuni Infected Mice Harboring a Human Gut Microbiota

Abstract: Human campylobacteriosis constitutes a zoonotic food-borne disease and a progressively rising health burden of significant socioeconomic impact. We have recently shown that conventional mice are protected from Campylobacter jejuni infection, which was not the case for human microbiota associated (hma) mice indicating that the host-specific gut microbiota composition primarily determines susceptibility to or resistance against C. jejuni infection. In our present preclinical intervention study we addressed wheth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Murine fecal microbiota transplantation treatment was shown to alleviate intestinal and systemic immune responses in C. jejuni-infected mice harbouring a human gut microbiota. These with mice displayed higher numbers of lactobacilli and bifidobacteria, further suggesting the beneficial effects of probiotics against pathogen colonisation [39]. However, a prerequisite for survival in the intestinal tract is the ability of probiotic strains to transiently adhere efficiently to the intestinal mucosa.…”
Section: Combined Effect Of Gmo and B Infantis On C Jejuni Adhesionmentioning
confidence: 95%
See 1 more Smart Citation
“…Murine fecal microbiota transplantation treatment was shown to alleviate intestinal and systemic immune responses in C. jejuni-infected mice harbouring a human gut microbiota. These with mice displayed higher numbers of lactobacilli and bifidobacteria, further suggesting the beneficial effects of probiotics against pathogen colonisation [39]. However, a prerequisite for survival in the intestinal tract is the ability of probiotic strains to transiently adhere efficiently to the intestinal mucosa.…”
Section: Combined Effect Of Gmo and B Infantis On C Jejuni Adhesionmentioning
confidence: 95%
“…The ability of B. infantis ATCC 15697 to use multiple specific carbohydrate structures (2′FL, LNT, 3′SL, 6′SL, DSL, LNH, Sialic Acid, LSTc, LNnT and LNnH) within the pool was also Previous studies have demonstrated statistically significant increases in Bifidobacterium and Bacteroides growth following incubation with GMO [12]. Similarly, GMO has also been shown to increase levels of bifidobacteria using in vitro fermentation models and in in vivo mouse trials [15,39]. The prebiotic effect observed here is not surprising given that B. infantis ATCC 15697 is particularly adept at the utilising human milk glycans due to the presence of a 43 kb gene cluster responsible for their transport and utilization [56][57][58][59][60][61][62][63][64].…”
Section: Prebiotic Effects Of Gmomentioning
confidence: 96%
“…In summary, our present study revealed that peroral C. coli infection results in pronounced clinical signs, apoptotic, and pro-inflammatory immune responses in the intestinal tract of IL-10 −/− mice harboring a human intestinal microbiota, whereas IL-10 −/− mice with a murine intestinal microbiota were stably colonized by the pathogen, but protected from disease manifestations. Given that murine FMT treatment could effectively dampen pathogen-induced apoptotic epithelial and pro-inflammatory immune responses in the large intestines of C. jejuni -infected microbiota-depleted, as well as of “humanized”, IL-10 −/− mice [ 27 , 31 ], these findings collectively provide strong evidence that microbiota modifications by pre- or probiotics, for instance, might open novel avenues for future treatment strategies in the combat of campylobacteriosis in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Our cultural analyses and culture-independent molecular approaches additionally assessing fastidious and non-cultivable bacteria revealed, however, that the host-specific differences in numbers of the most common intestinal bacterial groups, genera, and species between respective fecal donor suspensions could also be observed in the intestinal tract of IL-10 −/− mice after establishment of the complex human versus murine intestinal microbiota following peroral FMT. Even though the methods applied here have their limitations regarding the possibilities to provide a complete picture of the commensal ecological conditions within the gut lumen, the combinatory approach of quantitative “culturomics” plus 16S rRNA-based analyses have been proven highly reliable for a comprehensive survey of differences in host-specific intestinal microbiota compositions [ 15 , 16 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. One needs to take into account, however, that during processing of the fecal donor samples, including freezing and thawing, individual bacterial strains might have been reduced and not fully established within the intestinal tract upon FMT [ 27 , 30 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with other investigators, we have recently shown that conventional mice bred in our specific pathogen-free (SPF) facilities are protected from stable gastrointestinal C. jejuni colonization even upon peroral infection with high doses. Upon modifying the murine gut microbiota (i.e., its virtual depletion) following broad-spectrum antibiotic treatment, and also upon re-association with human as opposed to murine gut microbiota by fecal microbiota transplantation, these mice can be effectively colonized by the pathogen upon peroral challenge and display typical histopathologic pro-inflammatory features of campylobacteriosis in their intestines [46][47][48][49], whereas the classic symptoms such as abdominal cramps, watery, or bloody diarrhea seen in infected humans were missing in conventional wildtype mice without genetic manipulations [46] (Figure 4).…”
Section: Figurementioning
confidence: 99%